2005
DOI: 10.1590/s1415-47572005000300023
|View full text |Cite
|
Sign up to set email alerts
|

Comet assay comparison of different Corbicula fluminea (Mollusca) tissues for the detection of genotoxicity

Abstract: The comet assay was used to study the sensitivity of the widely distributed freshwater bivalve mollusk Corbicula fluminea to the DNA-damaging alkylating-agent methylmethane sulfonate (MMS). This study was undertaken to ascertain if C. fluminea is a good bioindicator of pollutants in aquatic environments and identify which C. fluminea tissue is most effective and practical for genotoxicity studies. The mollusks were exposed to 0.6, 1.2 or 2.4 X 10 -4 M MMS for 40 min and their hemolymph, gill tissue and digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 20 publications
2
33
0
4
Order By: Relevance
“…Comparing these results with those for the in vitro assays suggests that whole organisms can process and minimize the effects of contaminants more efficiently that cells in culture (Table 1, Figure 2 a). Our results indicate that C. fluminea and CHO k1 cells are good models for biomonitoring fresh water environments using the comet assay, supporting the work of other authors (Matsumoto et al, 2003;Rigonato et al, 2005). The high comet scores, and hence damage, in the cells treated with river water as compared to the negative control could be attributed to the action of industrial and urban discharges carried by the Paraná river water.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Comparing these results with those for the in vitro assays suggests that whole organisms can process and minimize the effects of contaminants more efficiently that cells in culture (Table 1, Figure 2 a). Our results indicate that C. fluminea and CHO k1 cells are good models for biomonitoring fresh water environments using the comet assay, supporting the work of other authors (Matsumoto et al, 2003;Rigonato et al, 2005). The high comet scores, and hence damage, in the cells treated with river water as compared to the negative control could be attributed to the action of industrial and urban discharges carried by the Paraná river water.…”
Section: Resultssupporting
confidence: 88%
“…These clams are an optimal in vivo biomonitor for aquatic environments due to their high filtration rates, ease of collection and the fact that their laboratory maintenance is simple (Cataldo et al, 2001). The bioaccumulation capacity of C. fluminea in bioassays has been reported by several workers (Bilos et al, 1998;Rigonato et al, 2005). Furthermore, a study of the lower Paraná River showed a high mortality of young C. fluminea in regions contaminated with urban and industrial effluents, suggesting that this bivalve could be a reliable indicator of water quality (Cataldo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The high concentration and prolonged exposure time damaged the repair mechanism in the severely damaged cells, hence failed to repair, and their frequency remain higher at higher concentration after 28 days of treatment. Janaina et al (2005) recorded the similar comet classes in Corbicula fluminea (Mollusca) tissues exposed to methyl methane sulfonate for 40 min to concentration of 0.6, 1.2 or 2.4 9 10 -4 M. They used hemolymph, gill and digestive gland tissues to evaluate the DNA damage and found the highest damage in the gill tissues with all the comet classes from no damage to severe damage. Further, Hoshina and Marin-Morales (2010) also uses the comet classes to demonstrate the damage to DNA in the erythrocytes of Oreochromis niloticus sampled in the water with petroleum refinery effluents of Atibaia and Jaguarí rivers.…”
Section: Discussionmentioning
confidence: 99%
“…The damage score was calculated as the sum of cells in each class and the total number of cells in each class multiplied by the number of classes (0-3). Scores range from zero (all cells with no damage-0×100) to 300 (all cells with maximum damage 3×100), Rigonato et al (2005) (Table 1).…”
Section: Resultsmentioning
confidence: 99%